PENDIDIKAN ISLAM VERSUS GLOBALISASI PENDIDIKAN - Nelly . (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2018)
The research has two points of discussion. First, Islamic contribution on world education thought and practice (dominated by Islamic history). Furthermore, the original Islamic concept (al-quran and Sunnah) and the role of Muhammad and other Islamic leaders (Khulafaur Rasyidin, Daulah Umayyah, Daulah Abbasiyah, and so on) as a pioneer of academic tradition, being an inspiration to knowledge civilization. The proof of Islam as a leading sector of knowledge and civilization in western world, such as Europe, was the emergence of multidisciplinary-knowledge from Islamic scholars, not only on theology. This turmoil, then, continued to Islamic education institution such as Madrasah Nizamiyyah in Baghdad (450 H/1069 M) as the symbol of sect, mazhab, and religionism preservation. Second, focusing on Islamic education map in this globalization era, there are five greatetest trends dominantly on Islamic thought typhology: fundamentalism, traditionality, reformism, post-traditionality, and modernism.